Hepatic Cysts: Reappraisal of the Classification, Terminology, Differential Diagnosis, and Clinicopathologic Characteristics in 258 Cases. (4th September 2022) - Armutlu, Ayse; Quigley, Brian; Choi, Hegyong; Basturk, Olca; Akkas, Gizem; Pehlivanoglu, Burcin; Memis, Bahar; Jang, Kee-Taek; Erkan, Mert; Erkan, Burcu; Balci, Serdar; Saka, Burcu; et al.
Abstract : The literature on liver cysts is highly conflicting, mostly owing to definitional variations. Two hundred and fifty-eight ≥1 cm cysts evaluated pathologically using updated criteria were classifiable as: I. Ductal plate malformation related (63%); that is, cystic bile duct hamartoma or not otherwise specified-type benign biliary cyst (35 with polycystic liver disease). These were female predominant (F/M=2.4), large (10 cm), often multifocal with degenerative/inflammatory changes and frequently misclassified as "hepatobiliary cystadenoma." II. Neoplastic (13%); 27 (10.5%) had ovarian-type stroma (OTS) and qualified as mucinous cystic neoplasm (MCN) per World Health Organization (WHO). These were female, solitary, mean age 52, mean size 11 cm, and 2 were associated with carcinoma (1 in situ and 1 microinvasive). There were 3 intraductal papillary neoplasms, 1 intraductal oncocytic papillary neoplasm, 1 cystic cholangiocarcinoma, and 2 cystic metastasis. III. Infectious/inflammatory (12%). These included 23 hydatid cysts (including 2 Echinococcus alveolaris both misdiagnosed preoperatively as cancer), nonspecific inflammatory cysts (abscesses, inflammatory cysts: 3.4%). IV. Congenital (7%). Mostly small (<3 cm); choledochal cyst (5%), foregut cyst (2%). V. Miscellaneous (4%). In conclusion, hepatic cysts occur predominantly in women (3/1), are mostly (90%) non-neoplastic, and seldom (<2%) malignant. Cystic bile duct hamartomas and their relative not otherwise specified-type benign biliary cysts are frequently multifocal and often misdiagnosed as "cystadenoma/carcinoma." Defined by OTS, MCNs (the true "hepatobiliary cystadenoma/carcinoma") are solitary, constitute only 10.5% of hepatic cysts, and have a significantly different profile than the impression in the literature in that essentially all are perimenopausal females, and rarely associated with carcinoma (7%). Since MCNs can only be diagnosed by demonstration of OTS through complete microscopic examination, it is advisable to avoid the term "cystadenoma/cystadenocarcinoma" solely based on radiologic examination, and the following simplified terminology would be preferable in preoperative evaluation to avoid conflicts with the final pathologic diagnosis: (1) noncomplex (favor benign), (2) complex (in 3 subsets, as favor benign, cannot rule out malignancy, or favor malignancy), (3) malignant features.